Making sense of 'teaching', 'support' and 'differentiation': the educational experiences of pupils with Education, Health and Care Plans and Statements in mainstream secondary schools. Issue 1 (1st January 2019) - Webster, Rob; Blatchford, Peter
Abstract: This paper reports on results from a descriptive study of the nature and quality of the day-to-day educational experiences of 49 13–14 year olds with special education needs and/or disabilities (SEND). All pupils had either an Education Health and Care Plan (EHCP) or a Statement, and attended in mainstream secondary school in England. Pupils involved in the SEN in Secondary Education study were shadowed for several days over a school week. Researchers prepared pupil-level case studies on the basis of data from qualitative observations and semi-structured interviews with pupils and key school staff involved in their learning and development. The case studies were subjected to a thematic analysis. Results are presented in terms of two inter-related themes – (i) teaching and support; and (ii) differentiation – which address approaches to, and expressions of, inclusive practice; the roles of teachers and teaching assistants; and the defining features of teaching and support for SEND. The results are considered in view of the inclusiveness, appropriateness and effectiveness of provision on offer to pupils with high-level SEND. We conclude there has been a systemic and long-standing failure to fully address the educational needs of such pupils, and suggest what schools could do to provide higher quality experiences.